A novel SPECT camera for molecular imaging of the prostate - Cebula, Alan; Gilland, David; Su, Li-Ming; Wagenaar, Douglas; Bahadori, Amir A. (SPIE, 2011)
The objective of this work is to develop an improved SPECT camera for dedicated prostate imaging. Complementing the recent advancements in agents for molecular prostate imaging, this device has the potential to assist in distinguishing benign from aggressive cancers, to improve site-specific localization of cancer, to improve accuracy of needle-guided prostate biopsy of cancer sites, and to aid in focal therapy procedures such as cryotherapy and radiation. Theoretical calculations show that the spatial resolution/detection sensitivity of the proposed SPECT camera can rival or exceed 3D PET and further signal-to-noise advantage is attained with the better energy resolution of the CZT modules. Based on photon transport simulation studies, the system has a reconstructed spatial resolution of 4.8 mm with a sensitivity of 0.0001. Reconstruction of a simulated prostate distribution demonstrates the focal imaging capability of the system.
Citation: Proc. SPIE 8143, Medical Applications of Radiation Detectors, 814305 (September 14, 2011); doi:10.1117/12.896235
Keywords: Single Photon Emission Computed Tomography (SPECT); Prostate Imaging, Cadmium Zinc Telluride (CZT)